(3QYGjI GdCeheI aj GdbGfhf GdeUQj GdebGQf (B/ s - (3eMeO eUdM eMeO RbRhbs; (3eMeO CMeO ESeGYjd (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2007)
(3JTcd GdeQCI fUa GdeLJeY h efP aLQ GdJGQjN cGfJ GdYehO GdabQi ddCSQI hGdeLJeY GjVG h dG JRGd NjQ SfO hOYe ddQLd ai SGFQ eQGMd JWhQ GdHTQjI (B: (3Jba HLhGQg JTO ef GRQg hJSGYOg Ydi JOHjQ GehQg GdMjGJjI h JTGQcg ai Yedg aVdG Yf GdJRGegG Gh hXjaJgG GdGSGSjI aj Jhdi GYeGd GdefRds
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2007.s
(3HHdjhLQGajG(B: (3UaMGJ(B145-150.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3QYGjI GdCeheI s; (3GdbGfhf GdeUQj GdebGQfs; (3efXeI GdYed GdOhdjIs; (3CeheI GdeQCI GdYGedI s; (3eSJhjGJ GdYed GdYQHj s; (3GdMO GdCOfi ddJCejfGJ GdGLJeGYjIs; (3CLGRI GdCeheI s; (3eOI GdNOeI GdeDgdI ddGSJMbGb s; (3EYGfGJ GdCeheIs; (3Jehjd EYGfGJ GdCeheI s; (3MXQ GdaUd CKfGA CLGRI GdCeheI s; (3QYGjI GdWahdI s; (3GdEQVGY s; (3GdMVGfI s; (3ELGRI QYGjI GdWads; (3GdYGedI GdMGeds; (3QYGjI GdCeheI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2007